Clonal and resistance profiles of fluoroquinolone-resistant uropathogenic Escherichia coli in countries with different practices of antibiotic prescription - Choudhury, Debarati; Alanbari, Rawan; Saveliev, Pauline; Sokurenko, Evgeni; Fuzi, Miklos; Tchesnokova, Veronika (Frontiers in Microbiology, 2024)
Background. Antibiotic prescription practices vary between countries, influencing regional antimicrobial resistance prevalence. Yet, comparisons of clonal diversity among resistant bacteria in differently prescribing nations are rare. The rise of fluoroquinolone-resistant E. coli (FQREC), often multidrug-resistant, exacerbates global antibiotic resistance. Unlike the USA, antibiotics are commonly dispensed in Iraq without prescriptions, fostering widespread overuse and misuse. This study was undertaken to understand the impact of varying antibiotic use practices on FQREC diversity.Methods. We compared FQREC prevalence, multidrug resistance, and clonality of FQREC among E. coli isolated from urine submitted in 2017-2018 to three US hospitals and two in Iraq. All FQREC isolates were analyzed for QRDR mutations and PMQR gene presence. Subset of FQREC strains belonging to ST131-H30R/Rx sub-groups, underwent whole genome sequencing and phylogenetic analysis.Results. Iraqi E. coli showed significantly higher resistance to all tested antibiotics compared to those from the USA, with 76.2% being FQREC, versus 31.2% in the USA (P<.01). Iraqi FQREC were more frequently multidrug-resistant. The predominant sub-group in both countries was ST131-H30, with the notable absence of ST1193 among Iraqi FQREC. Iraqi-origin ST131-H30 strains exhibited higher MIC values for ciprofloxacin and greater resistance to 3GC, TMP/STX, and IMI compared to those from the USA. The increased 3GC resistance in Iraqi strains was linked to a higher proportion of blaCTX-M15-carrying H30Rx sub-clade isolates. Iraqi H30 strains also tended to have higher MICs for FQ, attributed to their more frequent carriage of PMQR determinants compared to US strains.46 Iraqi and 63 US H30 isolates underwent WGS. The tree revealed two clades -H30R and H30Rx in both countries, with Iraq and US isolates distributed without forming a distinct new major subclone. Iraqi isolates tended to cluster together in separate subclades, indicating endemic circulation of the strain groups.In regions like Iraq, where antibiotics are overused and misused, there's a significant increase in resistance among uropathogenic E. coli to various antibiotics. Most Iraqi resistant strains belong to major international groups, with no new highly successful strains emerging. The absence of ST1193 suggests regional, socioeconomic, demographic, or cultural barriers hindering certain strain groups' success in Iraq.